Environmentally-driven gene content convergence and the Bacillus phylogeny - Ismael L. Hernández-González (BMC Evolutionary Biology, 2018)
Abstract Background Members of the Bacillus genus have been isolated from a variety of environments. However, the relationship between potential metabolism and the niche from which bacteria of this genus have been isolated has not been extensively studied. The existence of a monophyletic aquatic Bacillus group, composed of members isolated from both marine and fresh water has been proposed. Here, we present a phylogenetic/phylogenomic analysis to investigate the potential relationship between the environment from which group members have been isolated and their evolutionary origin. We also carried out hierarchical clustering based on functional content to test for potential environmental effects on the genetic content of these bacteria. Results The phylogenetic reconstruction showed that Bacillus strains classified as aquatic have evolutionary origins in different lineages. Although we observed the presence of a clade consisting exclusively of aquatic Bacillus, it is not comprised of the same strains previously reported. In contrast to phylogeny, clustering based on the functional categories of the encoded proteomes resulted in groups more compatible with the environments from which the organisms were isolated. This evidence suggests a detectable environmental influence on bacterial genetic content, despite their different evolutionary origins. Conclusion Our results suggest that aquatic Bacillus species have polyphyletic origins, but exhibit convergence at the gene content level.